Perencanaan Pengembangan Kawasan Perdesaan Berbasis Potensi di Bagian Selatan Provinsi Jawa Timur (Studi: Kabupaten Banyuwangi) - Herman Cahyo Diartho; Endah Kurnia Lestari; Duwi Yunitasari; Agus Lutfi; Fivien Muslihatinningsih (MediaTrend, 2020)
Rural development becomes important as an effort to minimize disparitiesbetween regions. The purpose of this study is to analyze the economic potentialin rural areas and design policies in Banyuwangi Regency, especially in thesouthern part. The method used to analyze data is Location Quotient (LQ)analysis. Sampling data taken in 10 districts in Banyuwangi Regency. TheBanyuwangi Regency was chosen because it was included in the largest foodgranary in East Java. The analysis shows that each sub-district has a superiorsector each, namely certain commodities that have a competitive advantagecompared to other districts.